Pengaruh Opini Audit Tahun Sebelumnya, Opinion Shopping, Reputasi Kap dan Audit Tenure terhadap Opini Audit Going Concern (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2020-2023): Penelitian - Erika Verdiantanty; Hendri Setyawan (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
This study aims to provide empirical evidence regarding the influence of the prior year's audit opinion, opinion shopping, firm reputation, and audit tenure on the going-concern audit opinion. The population of 220 manufacturing companies listed on the Indonesia Stock Exchange for the 2020-2023 period was 220. This study used a purposive sampling technique. From the existing population, 134 manufacturing companies were selected that met the established criteria over a four-year period. The sample size was 134 companies x 4 years = 536 company data. This study used independent audit report data. The analysis used logistic regression analysis. The results of this study indicate that the prior year's audit opinion and firm reputation have a significant positive effect on the going-concern audit opinion, while opinion shopping and audit tenure do not significantly influence the going-concern audit opinion.